Modelling health risks of urine-derived fertiliser application in urban green areas using quantitative microbial risk assessment - Johanna M. Engels; Frederic Leusch; Phil Choi; Patrick Smeets (Bioresource Technology, 2026)

In-depth characterization of tertiary cellulose from wastewater treatment facilities - Ana Luiza Slama de Freitas; Tim G.W. Engels; Salvador Bertran Llorens; Alessia Lasorsa; Patrick C.A. van der Wel; Hero J. Heeres; Peter J. Deuss (Biomass and Bioenergy, 2026)

Chemical contamination of black soldier fly larvae raised on EU-authorized or unauthorized substrate - Marie Papin; Maxime Pattier; Mélanie Davranche; Patrick Borel; Erwan Engel; Christelle Planche (Waste Management, 2026)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

The effect of climate at origin on Douglas-fir growth, leaf traits and embolism resistance along a rainfall gradient in Central Europe - Vincent P. Riedel; Patrick Engel; Pierre-André Waite; Roman M. Link; Randolf Schirmer; Joachim Hamberger; Bernhard Schuldt (Trees, 2025)
Key message In Douglas-fir grown in Central Europe, growth and specific leaf area differed between coastal and interior provenances but little intra-specific variability was found for the Huber value and xylem safety. Abstract In Central Europe, the economically most important timber species for roundwood production, Norway spruce, has been severely affected by recent global change-type drought events. Due to its large spatial distribution, Douglas-fir ( Pseudotsuga menziesii ) is considered for conversion to climate-resilient forests. Specifically, provenances from moister coastal and drier and colder interior regions might differ in drought tolerance traits. Here, we characterized aboveground biomass increment as well as leaf morphological and plant hydraulic traits in mature trees of 28 Douglas-fir provenances from three climate-at-origin groups across a climatic gradient in Central Europe, covering a precipitation range of 542 mm yr −1 . Irrespective of the gradient, the northern interior provenances had a 5.4 kg yr −1 lower aboveground biomass increment than the two coastal groups, accompanied by a 13% smaller specific leaf area. On the other hand, the Huber value, embolism resistance ( P 50 ) and leaf carbon isotope signature (δ 13 C) as proxy for long-term intrinsic water use efficiency did not differ between climate-origin groups. Across the gradient and within a climate-origin-group, no effect of climatic aridity on any of the traits covered was observed. Especially P 50 showed very little intra-specific variability, and our observed mean of −3.5 MPa is in the same range as P 50 -values for Douglas-fir recently reported from Europe. Our results for Douglas-fir support that xylem safety is a rather conservative and evolutionary canalized trait in conifers, while the Huber value revealed less plasticity as expected. Future studies are needed to test whether slower-growing interior provenances with thicker and smaller needles might be more drought tolerant and thus better suited for cultivation in the future climate of Central Europe although xylem safety does not differ.

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Declining morphological diversity in snakefly larvae during last 100 million years - Joachim T. Haug; Michael S. Engel; Patrick Mendes dos Santos; Gideon T. Haug; Patrick Müller; Carolin Haug (PalZ, 2022)
Raphidioptera, the group of snakeflies, is a rather species-poor in-group of Holometabola. Yet, fossils of snakeflies indicate that the group was more diverse in the past. Here we compare the morphological diversity of snakefly larvae over time. Snakefly larvae are well represented in Cretaceous and Eocene ambers facilitating such a comparison. We used measurements of discrete dimensions as a basis for comparison. This reveals a larger diversity of snakefly larvae in the Cretaceous, especially in relation to head shapes and morphology of the antennae, which were much more variable. In particular, some Cretaceous larvae possessed greatly elongated head capsules and uniquely long and prominent antennae, unparalleled among modern forms. Already by the Eocene, snakefly larvae were less variable than those of the Cretaceous, although some still possessed longer antennae than modern-day larvae. The loss of morphological diversity supports the already well-established loss of taxonomic diversity in the group across time. Quite likely, this also indicates a loss of ecological diversity. These results are comparable to losses in different lineages of the closely related group Neuroptera.

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Salivary nitrate/nitrite and acetaldehyde in humans: potential combination effects in the upper gastrointestinal tract and possible consequences for the in vivo formation of N-nitroso compounds—a hypothesis - Gerhard Eisenbrand; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; et al. (Archives of Toxicology, 2022)

Contribution to the ongoing discussion on fluoride toxicity - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2021)
Since the addition of fluoride to drinking water in the 1940s, there have been frequent and sometimes heated discussions regarding its benefits and risks. In a recently published review, we addressed the question if current exposure levels in Europe represent a risk to human health. This review was discussed in an editorial asking why we did not calculate benchmark doses (BMD) of fluoride neurotoxicity for humans. Here, we address the question, why it is problematic to calculate BMDs based on the currently available data. Briefly, the conclusions of the available studies are not homogeneous, reporting negative as well as positive results; moreover, the positive studies lack control of confounding factors such as the influence of well-known neurotoxicants. We also discuss the limitations of several further epidemiological studies that did not meet the inclusion criteria of our review. Finally, it is important to not only focus on epidemiological studies. Rather, risk analysis should consider all available data, including epidemiological, animal, as well as in vitro studies. Despite remaining uncertainties, the totality of evidence does not support the notion that fluoride should be considered a human developmental neurotoxicant at current exposure levels in European countries.

Toxicity of fluoride: critical evaluation of evidence for human developmental neurotoxicity in epidemiological studies, animal experiments and in vitro analyses - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2020)
Recently, epidemiological studies have suggested that fluoride is a human developmental neurotoxicant that reduces measures of intelligence in children, placing it into the same category as toxic metals (lead, methylmercury, arsenic) and polychlorinated biphenyls. If true, this assessment would be highly relevant considering the widespread fluoridation of drinking water and the worldwide use of fluoride in oral hygiene products such as toothpaste. To gain a deeper understanding of these assertions, we reviewed the levels of human exposure, as well as results from animal experiments, particularly focusing on developmental toxicity, and the molecular mechanisms by which fluoride can cause adverse effects. Moreover, in vitro studies investigating fluoride in neuronal cells and precursor/stem cells were analyzed, and 23 epidemiological studies published since 2012 were considered. The results show that the margin of exposure (MoE) between no observed adverse effect levels (NOAELs) in animal studies and the current adequate intake (AI) of fluoride (50 µg/kg b.w./day) in humans ranges between 50 and 210, depending on the specific animal experiment used as reference. Even for unusually high fluoride exposure levels, an MoE of at least ten was obtained. Furthermore, concentrations of fluoride in human plasma are much lower than fluoride concentrations, causing effects in cell cultures. In contrast, 21 of 23 recent epidemiological studies report an association between high fluoride exposure and reduced intelligence. The discrepancy between experimental and epidemiological evidence may be reconciled with deficiencies inherent in most of these epidemiological studies on a putative association between fluoride and intelligence, especially with respect to adequate consideration of potential confounding factors, e.g., socioeconomic status, residence, breast feeding, low birth weight, maternal intelligence, and exposure to other neurotoxic chemicals. In conclusion, based on the totality of currently available scientific evidence, the present review does not support the presumption that fluoride should be assessed as a human developmental neurotoxicant at the current exposure levels in Europe.

Markers of biological stress in response to a single session of high-intensity interval training and high-volume training in young athletes - Yvonne Kilian; Florian Engel; Patrick Wahl; Silvia Achtzehn; Billy Sperlich; Joachim Mester (European Journal of Applied Physiology, 2016)

The neuroinvasive profiles of H129 (herpes simplex virus type 1) recombinants with putative anterograde-only transneuronal spread properties - Gregory J. Wojaczynski; Esteban A. Engel; Karina E. Steren; Lynn W. Enquist; J. Patrick Card (Brain Structure and Function, 2015)

Colorectal surveillance in Lynch syndrome families - Wouter H. de Vos tot Nederveen Cappel; Heikki J. Järvinen; Patrick M. Lynch; Christoph Engel; Jukka-Pekka Mecklin; Hans F. A. Vasen (Familial Cancer, 2013)

A GIS-based Model of the Distribution of the Rare Liverwort Aneura maxima at the Landscape Scale for an Improved Assessment of Its Conservation Status - Alain Vanderpoorten; André Sotiaux; Patrick Engels (Biodiversity and Conservation, 2006)

Alanine dehydrogenase from the psychrophilic bacterium strain PA-43: overexpression, molecular characterization, and sequence analysis - Jane A. Irwin; Susan V. Lynch; Suzie Coughlan; Patrick J. Baker; Haflidi M. Gudmundsson; Gudni A. Alfredsson; David W. Rice; Paul C. Engel (Extremophiles, 2003)

Patterns of bryophyte diversity and rarity at a regional scale - Alain Vanderpoorten; Patrick Engels (Biodiversity and Conservation, 2003)